2023
DOI: 10.3390/aerospace10030262
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Resolution of Blade Tip Vortices in Hover with High-Order WENO Scheme and Hybrid RANS–LES Methods

Abstract: The accurate prediction of blade tip vortices continues to be challenging for the investigation of rotor aerodynamics. In the current work, the blade tip vortex system of a Caradonna–Tung rotor in the hovering state is simulated on account of the framework of a high-order WENO scheme and hybrid RANS/LES method progressively. With the RANS method based on a fifth-order WENO–Roe scheme, the spatial resolution of wake age and capture the accuracy of tip vortices are improved significantly. However, the unsteadine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Both of the b tip vortex systems describe a helicoidal pattern. Based on the current spatial resoluti method, the rotor tip vortices of the baseline blade develop to the wake age of fou revolutions, which is close to the previous result[26] with the same method. Comp to the baseline blade, it is observed that the wake age of slotted blade lasted for only revolutions, which indicates the remarkable attenuation of vorticity strength.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Both of the b tip vortex systems describe a helicoidal pattern. Based on the current spatial resoluti method, the rotor tip vortices of the baseline blade develop to the wake age of fou revolutions, which is close to the previous result[26] with the same method. Comp to the baseline blade, it is observed that the wake age of slotted blade lasted for only revolutions, which indicates the remarkable attenuation of vorticity strength.…”
supporting
confidence: 82%
“…Other numerical methodologies are consistent with the RANS simulation. The capability of the method has been verified via a variety of cases about helicopter fuselage and rotating blade flow fields [25,26], where how a particular numerical scheme is affected by diffusion has been discussed in detail correspondingly.…”
Section: Numerical Methologymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 20 shows comparisons of the ALM results of blade tip vortex evolution in vertical and radial directions, where z/R and r/R represent the vertical position and the radial position. The full CFD results of the simulation with the RANS method based on a fifth-order WENO-Roe scheme [36] were adopted as a reference for comparison. It can be found that the ALM with the third-order solver (ALM3), due to lower numerical dissipation, predicts a better agreement with the experimental results for the vortex age up to 360 • .…”
Section: Hover Flight Rotormentioning
confidence: 99%